PENINGKATAN PENGETAHUAN KEPALA RUANGAN MELALUI EDUKASI PENERAPAN GAYA KEPEMIMPINAN EFEKTIF SEBAGAI UPAYA MENINGKATKAN KINERJA PERAWAT DI RUMAH SAKIT UMUM AISYIYAH PADANG - Asmawati, Asmawati; Oktizulvia, Conny (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2024)
The results showed that the leadership style of the head of the room affected not only the executive nurses' performance but also the health service system as a whole. Based on the study's results, it is known that the leadership style used by the head of the room is a combination of democratic leadership followed by autocratic and participatory. The purpose of community service is to increase the head of the room's knowledge regarding applying an effective leadership style to improve the performance of implementing nurses in providing nursing services. The activity was carried out through lecture-based education talks with interactive communication by 12 nurse managers. This community service activity was carried out for one day by providing lectured-based talks starting from preparation, activity implementation, and activity evaluation. The benefit of this community service is an effort to improve and equip the knowledge of the head of the room with how to apply an effective leadership style to improve nurse performance and the quality of nursing service in the hospital. The results of the activity showed an increase in the knowledge of the head of the room regarding effective leadership styles.